Fever in Returning Travellers Due to a Noninfectious Disease: Two Case Reports - Saul Miller; Kevin Gabel; Christine H Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Each year, increasing numbers of people from developed countries travel to developing countries. It is not rare for these travellers to experience illness during or following their trips. It has been estimated that fever is present in 25% of those who seek medical attention following travel. In the majority of cases, the focus of the investigations centre around an infectious etiology, which can lead to a delay in establishing the noninfectious cause of fever. Two cases of fever, which were due to a noninfectious disease, are reported in returning travellers.